The impact of the promotion of row planting on farmers’ teff yields in Ethiopia - Vandercasteelen, Joachim; Dereje, Mekdim; Minten, Bart; Taffesse, Alemayehu Seyoum (International Food Policy Research Institute, 2013)
We assess the impact of the promotion of row planting at reduced seed rate on farmers’ teff yields in Ethiopia. Results indicate that the program to scale-up row planting, on average, has a positive but moderate effect on teff yield. These findings, however, are in contrast with larger yield increases found on village demonstration plots, in more controlled settings, and with the expectations of teff farmers. The differences are linked to problems in the implementation of the program and of its recommendations, to methodological issues, and likely to over-optimism on the potential of row planting in real farm settings.